2016
DOI: 10.1016/j.cub.2016.01.045
|View full text |Cite
|
Sign up to set email alerts
|

The Initiator Methionine tRNA Drives Secretion of Type II Collagen from Stromal Fibroblasts to Promote Tumor Growth and Angiogenesis

Abstract: SummaryExpression of the initiator methionine tRNA (tRNAiMet) is deregulated in cancer. Despite this fact, it is not currently known how tRNAiMet expression levels influence tumor progression. We have found that tRNAiMet expression is increased in carcinoma-associated fibroblasts, implicating deregulated expression of tRNAiMet in the tumor stroma as a possible contributor to tumor progression. To investigate how elevated stromal tRNAiMet contributes to tumor progression, we generated a mouse expressing additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 25 publications
(34 reference statements)
0
69
0
Order By: Relevance
“…As we have previously shown that elevated tRNA i Met levels do not lead to upregulated protein synthesis, increased cell proliferation (Clarke et al, 2016), or altered energy metabolism (data not shown) we looked at the ability of this tRNA to influence other cell characteristics that are associated with cancer aggressiveness. Initially we compared the migratory behaviour of immortalised mouse embryonic fibroblasts (iMEFs), which overexpress tRNA i Met (iMEF.tRNA i Met ), with those expressing an empty vector as control (iMEF.Vector).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have previously shown that elevated tRNA i Met levels do not lead to upregulated protein synthesis, increased cell proliferation (Clarke et al, 2016), or altered energy metabolism (data not shown) we looked at the ability of this tRNA to influence other cell characteristics that are associated with cancer aggressiveness. Initially we compared the migratory behaviour of immortalised mouse embryonic fibroblasts (iMEFs), which overexpress tRNA i Met (iMEF.tRNA i Met ), with those expressing an empty vector as control (iMEF.Vector).…”
Section: Resultsmentioning
confidence: 99%
“…Thus it would seem natural to propose that this alteration to the tRNA repertoire would drive increased use of the AUG codon leading to upregulation of translation initiation and protein synthesis to support cancer cell growth and proliferation. However, a recent study in stromal fibroblasts indicate that elevated levels of tRNA i Met do not directly support increased cellular protein synthesis and proliferation (Clarke et al, 2016). Rather, increased tRNA i Met alters the fibroblast secretome to favour synthesis and secretion of certain collagens (particularly type II collagen) which are incorporated into the tumour extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that tRNAs play roles in modulating cell proliferation and cancer progression [15][16][17]. tRNA halves (tRHs) and tRNA-derived small RNA fragments (tRFs) belong to a novel class of sncRNAs that are generated through precise cleavage of tRNAs [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These phenotypes are mimicked by overexpression of the initiator methionine tRNA (tRNA i Met ), which is responsible for the selection of the correct start codon during translation initiation. In human breast epithelial cells, overexpression of tRNA i Met promotes increased metabolic activity and proliferation [66] and, in a recent study, a transgenic mouse carrying two extra copies of the tRNA i Met gene showed enhanced tumor growth and vascularisation [67]. The latter was mainly due to tRNA i Met -dependent secretion of type II collagen by stromal fibroblasts, which in turn promoted angiogenesis and was generally associated with the aggressiveness of primary ovarian tumors.…”
Section: Pr Ospects and Overviewsmentioning
confidence: 99%